Investigación-acción en estudiantes con dificultades psicosociales a través de terapias alternativas (Research, Society and Development, 2018)
Currently there are psychosocial diseases such as panic syndrome, anxiety and depression, which lead to the isolation of people, fear of new situations, loss of motivation and often school dropout. One of the ways to combat the problem is by improving the well-being of the students and this can be an incentive for improvement in relation to the mentioned diseases. Following is a line of research on alternative therapies in student well-being. This article aims to present an action research on students connected to the Messianic Church who reported that they had psychosocial diseases and who underwent a therapy called Johrei. A qualitative quantitative study was carried out in which 14 participants who received the therapy for 5 months were selected. 7 pacients were from the control group. There was an increase in the sensation of well-being informed by the participants of the research, decrease in the use allopathic medication and improvement of school performance.